PENGARUH STRATEGI BELAJAR HEURISTIK TERHADAP KETERAMPILAN KOMUNIKASI DAN HASIL BELAJAR KOGNITIF IPA (BIOLOGI) SISWA KELAS VIII MTs ARRAHMAH NW PRINGGARATA - Hervina Hervina; Siti Nurhidayati; Ervina Titi Jayanti (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2015)
Based on observations in class VIII MTs Arrahmah NW IPA Pringgarata in the leraning process, indicating a lack of ability of the students in disclosing information obtained during the learning process, not the task of writing well-structured and less communicative language and do not lead to a fundamental question that needs to be conducted to determine the effect of the strategy used. The purpose of this study was to determine the effect of the heuristic learning strategies to the communication skills and cognitive learning science (biology) student of class VIII MTs Arrahmah NW Pringgarata. This research is a quasi experimental population of all eighth grade student totaling 44 students spread in two classes. Sampling was carried out with saturated sampling techniques, data collection techniques used were observation and tests. The data analysis of the percentage of communication skills in students of class VIII A at the first meeting of 78.12% with skilled category and 87.5% in the second meeting with the highly skilled category. Based on the results of hypothesis test, it obtained that t-count (2.38) greater than the price of the t-table (1.68). This shows that the heuristic strategies affect the communication skills and the cognitive learning science (biology) in class VIII MTs Arrahmah NW Pringgarata.